Dendritic Cells Require PINK1-Mediated Phosphorylation of BCKDE1α to Promote Fatty Acid Oxidation for Immune Function - Basit, Farhan; de Vries, I. Jolanda M. (Frontiers in Immunology, 2019)
Dendritic cell (DCs) activation by Toll-like receptor (TLR) agonist induces robust metabolic rewiring towards glycolysis. Recent findings in the field identified mechanistic details governing these metabolic adaptations. However, it is unknown whether switch to glycolysis from oxidative phosphorylation (OXPHOS) is a general characteristic of DCs upon pathogen encounter. Here we show that engagement of different TLR triggers differential metabolic adaptations in DCs. We demonstrate that LPS-mediated TLR4 stimulation induces glycolysis in DCs. Conversely, activation of TLR7/8 with protamine-RNA complex, pRNA, lead to increase in OXPHOS. Mechanistically, we found that pRNA stimulation phosphorylates BCKDE1α in a PINK1-dependent manner. pRNA stimulation increased branched-chain amino acid levels and increased fatty acid oxidation. Increased FAO and OXPHOS are required for DC activation. PINK1 deficient DCs switch to glycolysis to maintain ATP levels and viability. Moreover, pharmacological induction of PINK1 kinase activity primed immunosuppressive DC for immunostimulatory function. Our findings provide novel insight into differential metabolic adaptations and reveal important role of branched-chain amino acid in regulating immune response in DC.